Ascaris lumbricoides eggs or artefacts? A diagnostic conundrum. Issue 13 (12th November 2021) - Maurelli, M. P.; Alves, L. C.; Aggarwal, C. S.; Cociancic, P.; Levecke, B.; Cools, P.; Montresor, A.; Ianniello, D.; Gualdieri, L.; Cringoli, G.; Rinaldi, L.
Abstract: Abstract: Due to the presence of artefacts in stool samples, the copromicroscopic diagnosis of Ascaris lumbricoides is not always straightforward, particularly in the case of fertilized decorticated eggs. A total of 286 stool samples from 115 schoolchildren in India and 171 adult immigrants in Italy were screened for the presence of A. lumbricoides eggs by both Kato-Katz thick smear and Mini-FLOTAC. If the outer layer of A. lumbricoides eggs was absent, two aliquots of each stool sample were preserved: one for coproculture to identify larvae after development and one to compose a pool of stool for molecular analysis. A total of 64 stool samples (22.4%) were positive for A. lumbricoides using the Kato-Katz thick smear; 36 (56.3%) of these showed mammillated A. lumbricoides eggs, 25 (39.1%) showed elements resembling fertilized decorticated eggs, while three samples (4.7%) showed both mammillated and decorticated eggs. By Mini-FLOTAC, 39 stool samples (13.6%) were positive, while decorticated A. lumbricoides -like eggs were identified as artefacts. These results were confirmed by negative coprocultures and quantitative polymerase chain reaction. Mini-FLOTAC can be used for a reliable diagnosis of A. lumbricoides, thanks to the flotation and translation features which allow a clearer view, resulting in the correct identification of A. lumbricoides eggs.